2021
DOI: 10.1007/s00220-021-04220-w
|View full text |Cite
|
Sign up to set email alerts
|

Free Fermions Behind the Disguise

Abstract: An invaluable method for probing the physics of a quantum many-body spin system is a mapping to noninteracting effective fermions. We find such mappings using only the frustration graph G of a Hamiltonian H, i.e., the network of anticommutation relations between the Pauli terms in H in a given basis. Specifically, when G is (even-hole, claw)-free, we construct an explicit free-fermion solution for H using only this structure of G, even when no Jordan-Wigner transformation exists. The solution method is generic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 68 publications
(121 reference statements)
0
32
0
Order By: Relevance
“…This includes, as a special case, the Clifford transformations that we have analysed and thus puts our results in context by relating them to classifications of integrable models. We also treat the case of spin chains solvable by transforming to free fermions, making connections to recent papers on families of exactly solvable spin-1 /2 chains [24][25][26][27]. Finally, we discuss further avenues of research.…”
Section: Introductionmentioning
confidence: 97%
“…This includes, as a special case, the Clifford transformations that we have analysed and thus puts our results in context by relating them to classifications of integrable models. We also treat the case of spin chains solvable by transforming to free fermions, making connections to recent papers on families of exactly solvable spin-1 /2 chains [24][25][26][27]. Finally, we discuss further avenues of research.…”
Section: Introductionmentioning
confidence: 97%
“…Each spin model is defined by a Hamiltonian operator, and to every such Hamiltonian one can associate a graph, called its frustration graph. In [4] a new method is given that allows us to "solve a model" (meaning in this case to find the spectrum and the eigenvectors of the Hamiltonian) whose frustration graph is even-hole-free, claw-free, and has a simplicial clique. This augments earlier results of [1] where it is shown that models whose frustration graphs are line-graphs are solvable using certain classical tools.…”
Section: Introductionmentioning
confidence: 99%
“…This augments earlier results of [1] where it is shown that models whose frustration graphs are line-graphs are solvable using certain classical tools. The solution method of [4] uses only the structure of the frustration graph, and it is an extension of both [5] and [6]. The authors of [4] raised a question:…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations

A note on simplicial cliques

Chudnovsky,
Scott,
Seymour
et al. 2020
Preprint